answersLogoWhite

0


Best Answer

It is an equation and the value of t is 1

User Avatar

Wiki User

โˆ™ 2012-09-20 15:12:49
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 9 equals 5 plus 4t?
Write your answer...
Submit
Sign up for more answers

Registered users can ask questions, leave comments, and earn points for submitting new answers.

Already have an account? Log in

Related questions

5 plus what equals 14?

9


5 plus 4 equals 9 and 4 plus 5 equals 9 is an example of what property of addition?

Commutative


What is the value of x plus 4 equals 9?

5. Just do 9 minus 4. 5 plus 4 equals 9


5 plus 9 equals 9 plus 5 is an example of what?

5 +9 = 9 + 5 is an example of arithmetic commutativity


What does 4 plus 5 equals?

it equals 9


If 5 plus 3 equals 28 9 plus 1 equals 810 8 plus 6 equals 214 5 plus 4 equals?

19


2 plus 5 plus 9 plus 99 equals?

2 + 5 + 9 + 99 = 115


If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 9 plus 7 equals 96 9 plus 7 equals what?

96


What is 9 plus 5-1?

13...... 9 plus 5 equals 14...... 14 minus 1 equals 13


How does 9 plus 5 equals 2?

9+5=14 divided by 7 equals 2


A plus B equals nine?

4+5=9


If 5 plus 3 plus 2 equals 151012 9 plus 2 plus 4 equals 183662 8 plus 6 plus 3 equals 482466 and 5 plus 4 plus 5 equals 202504 Then 7 plus 2 plus 5 equals?

7+2+5= 14 35 42


What is 9 plus 5 plus 7 equals?

21


5 plus 7 plus 9 equals?

21


Which pair of values is the solution to the system of equations below r plus 2t equals -3 and 3r-4t equals -9?

r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)


2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 Then 9 plus 7 equals?

If I am correct, 9 plus 7 equals 112.


If 5 plus 3 equals 28 9 plus 1 equals 810 8 plus 6 equals 214 5 plus 4 equals 19 Then 7 plus 2 equals?

59


What is 2x plus 9 equals 4x plus 5 equal?

X equals 2 :)


5 plus 4 equals?

5 + 4 = 9


If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 and 8 plus 4 equals 96 then 9 plus 7 equals?

144 9+7 = 16 and 9*16 = 144


6 plus 9 plus 7-5 equals?

6+9+7-5=17 that is the answer


What is 5 plus 4 - 4 equals 9 plus m?

the answer to that is 5


What is 9 plus 9 plus 8 plus 8 plus 5 plus 5 plus 6 plus 4 plus 2 plus 2 equals?

58


Y equals -4 plus 5 y equals 3-9?

y = -2/5


What the answer to -2 plus 5 equals -9?

-2+5=3